Christian Educators as Independent, Youthful Leaders in the Era of Society 5.0 - Marthen Mau; Markus Amid (Badan Penerbit STIEPARI Press, 2025)
In general, Christian educators consider themselves not leaders, so they do not have the skills to influence the people they lead in advancing an organization. Therefore, the purpose of this study is to provide encouragement to Christian educators (teachers and lecturers) to believe in their calling as independent, young leaders to lead in the era of society 5.0. This paper uses a qualitative method through a literature approach to produce an understanding of Christian educators as independent, young leaders in the era of society 5.0. So, the results found are that Christian educators are increasingly disciplined in leading organizations or institutions, so that the people they lead will be increasingly responsible for the tasks they carry out.